Faecal Indicator Organisms in Frozen Prawn Products: 1. Incidence and General Distribution - Lekshmy, A; Pillai, V K (Fishery Technology, 1964)
A general survey carried out on several brands of frozen prawn products has shown that along with the standard plate count (SPC), the numbers of pathogenic organisms like Escherichia coli, enterococci and coagulase positive staphylococci have also to be taken into consideration for the evaluation of the quality of these products. No correlation could be established between the total plate count and the numbers of E. Coli, enterococci or staphylococci. Enumeration of enterococci, however, is advocated as a better index of faecal contamination of the products than E. Coli.